Influence of Socio-Demographic Factors and Knowledge of Family Planning on Fertility Preference among Married Men in Nigeria - Uyi E. OSADOLOR; Akinyimika O. SOWUNMI; Emmanuel O. AMOO (Communications of International Proceedings, 2021)
Fertility has been consistently high in Nigeria for the past decades and most studies addressing fertility issues in Nigeria focus mainly on women neglecting the role men play in fertility decisions. This study examines the effects of selected background factors and knowledge of family planning on fertility preference among married men in Nigeria. Using the 2013 Nigeria Demographic and Health Survey (NDHS) men’s dataset, the relationship between married men’s fertility preference and socio-demographic factors and knowledge of family planning were examined. Most married men (86.4%) report desiring more children, and 92.9% report 4 or more children as ideal number of children while only 7.1% report 3 or less children as ideal number of children. The older married men get, the more likely they desire no more children. Urban dwellers are more likely to desire no more children and want less than 4 children than rural dwellers. The likelihood to desire no more children and want less than 4 children increased as married men get more education. Christians are more likely to desire no more children and want less than 4 children than Muslims/Traditionalists. Working respondents were more likely to desire no more children than those not working. Married men who have knowledge of modern contraceptives are more likely to desire no more children than those who have knowledge of folkloric/traditional/no knowledge of contraceptive methods. The results are indicative of the need to do more segmentation programming and intervention in order to change attitudes and behaviour of sub-groups of married men towards managing fertility in Nigeria. This study identifies men’s preferences that fosters high fertility and recommends strategies in policy and programme interventions to curb fertility in Nigeria.
Keywords: Fertility Preference; Ideal Children; Family Planning Knowledge; Socio-demographic